The locus of the centre of the circle for which one end of the diameter is (3,3) while the other end lies on the line x+y=4.

2 years ago

Share

Answers : (1)

                                        

let (h,k) be the centre of the circle and other end of diameter be (x1,y1).


h= (x1+3)/2      and        k= (y1+3)/2


or, x1=2h-3       and        y1=2k-3


but (x1,y1) lie on x+y=4,


(2h-3)+(2k-3)=4


or, h+k=5


for locus, replace (h,k) by (x,y)..


thus, locus is  x+y=5


 

2 years ago

Post Your Answer

More Questions On Analytical Geometry

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
wat are asymptotes?
 
 
Asymptotes are tangents to a hyperbola which never really touch it or mathematically u can say touch it at infinity Asymptotes are very imp from jee pt of view so do it very nicely good luck...
 
needhelp 5 months ago
Area of a quadrilateral is 3/4*root3. The radius of circle circumscribing the quad. is 1. if AB=1 BD=root3 then BC.CD=?
 
 
Hello Student, clearly Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 5 months ago
Tangents are drawn from the point (α,β) to the hyperbola 3x 2 -2y 2 =6 and are inclined at angles θ and φ to the x-axis. If tanθ.tanφ =2, prove that β 2...
 
 
please check the attached file
  img
Sunil Raikwar 10 months ago
 
Hi Pranjal, There is slight technical issue. Please post these questions again in analytical Geometry. We will upload the answers for the same. askIITians Faculty
 
sunil raikwar 10 months ago
 
Given equation is Equations of tangents are the roots of this equation is therefore Thanks &Regards, Sunil Raikwar, askIITians faculty.
 
sunil raikwar 10 months ago
For all x in [0,90] show that cos(sinx)>sin(cosx) I understood the solution given in my book which said Cosx +sinx But then Cosx Then take sin and cos both sides resp we get two different...
 
 
Ans: Hello Student, Please find answer to your question below I am assuming you meant 90 to be pi/2. For sinx will take the value from 0 to 1 in increasing order. cosx will take the value...
  img
Jitender Singh 4 months ago
what is (x+3)(x -2)??
 
 
Hello Student, Please find the answer to your question (x + 3)(x – 2) = x^2+x-6 Hope that you will be satisfied with this
  img
Pankaj 5 months ago
 
absolutely correct. x(x – 2) + 3(x – 2) = x^2 – 2x + 3x – 6 = X^2 + x – 6 Hope that you both have understood now
  img
Pankaj 5 months ago
 
(x + 3)(x – 2) =x(x – 2) + 3(x – 2) = x^2 – 2x + 3x – 6 = X^2 + x – 6 Hope that you will understand now
  img
Pankaj 5 months ago
m=2-(3)^(1/2) Find the value of (m^6+m^5+m^4+1)/m^3
 
 
Hello student, This may help you m = 2 – 3^(1/2), and rationalising this we get m + 1/m = 4. som^2 = 4m-1 Given equation is= (m^3+1/m^3) +m^2+m From the identity if a+b+c = 0 gives...
  img
SHAIK AASIF AHAMED 4 months ago
 
Hello student, Please find the answer to your question below as m= m 2 =7- m 3 =26-15 1/m 3 =26+15 Given (m 6 +m 5 +m 4 +1)/m 3 =m+m 2+ m 3 +1/m 3 =2- +7-4 +26-15 +26+15 =61-5
  img
SHAIK AASIF AHAMED 4 months ago
 
m = 2 – 3^(1/2), and so m + 1/m = 4. We can also write this last equation as m^2 = 4m-1 Given expression = (m^3+1/m^3) +m^2+m Now, using the identity: a+b+c = 0 implies a^3+b^3+c^3 = 3abc,...
 
mycroft holmes 4 months ago
View all Questions »